Evaluasi program talent scouting guru SMK tahun 2013 Direktorat P2TK Dikmen Kemdikbud - Roudlotus Sholikhah; Soenarto Soenarto (Jurnal Pendidikan Vokasi, 2014)
Penelitian ini bertujuan untuk mengetahui: (1) relevansi pelaksanaan Program Talent Scouting Guru SMK tahun 2013 ditinjau dari aspek konteks; (2) kesesuaian pelaksanaan Program Talent Scouting Guru SMK tahun 2013 ditinjau dari aspek input; (3) efektifitas pelaksanaan Program Talent Scouting Guru SMK tahun 2013 ditinjau dari aspek proses; dan (4) pencapaian hasil pelaksanaan Program Talent Scouting Guru SMK tahun 2013 ditinjau dari aspek produk. Jenis penilitian ini adalah evaluasi program dengan model evaluasi CIPP (Context, Input, Process, Product). Hasil penelitian: (1) pencapaian relevansi program termasuk dalam kategori "sangat relevan" dengan persentase pencapaian 85%; (2) kesesuaian input SMK sasaran program, peserta program dan penyelenggara program termasuk dalam kategori "sesuai" dengan persentase pencapaian 76,38%; (3) keefektifan proses sosialisasi, seleksi dan pembekalan, proses pelaksanaan program serta proses monitoring dan pelaporan termasuk dalam kategori "efektif" dengan persentase pencapaian 74,52%; (4) pencapaian produk teaching dan non teaching termasuk dalam kategori "sangat tercapai" dengan persentase pencapaian 84,35%. AN EVALUATION OF THE TALENT SCOUTING PROGRAM FOR SMK TEACHERS IN 2013 DIREKTORAT P2TK DIKMEN KEMDIKBUDAbstractThis study aims to know: (1) the relevance of the Talent Scouting program for SMK teachers in 2013 in terms of the aspect of context, (2) the appropriateness of the Talent Scouting program for SMK teacher in 2013 in terms of the aspect of input, (3) the effectiveness of the Talent Scouting program for SMK teacher in 2013 in terms of the aspect of process, and (4) the attainment of the Talent Scouting program for SMK teacher in 2013 in terms of the aspect of product. This research is an evaluation of the program using CIPP (Context, Input, Process, Product) evaluation model. The results of this study: (1) the relevance of the program achievement is included in the category of "very relevant" with the achievement percentage of 85%, (2) the input appropriateness of vocational program targets, program participants and program providers are included in the category of "appropriate" with the percentage achieved is 76.38%, (3) the effectiveness of the process of socialization, selection and provisioning, implementation process, monitoring and reporting process are included in the category of "effective" with the achievement percentage of 74.52%, (4) teaching and non-teaching product attainment are included in the category of "very attainable" with the achievement percentage of 84.35%.